Growth factor and signaling pathways and their relevance to prostate cancer therapeutics - Wozney, Jocelyn L. (2014)
Treatments that target the androgen axis represent an effective strategy for patients with advanced prostate cancer, but the disease remains incurable and new therapeutic approaches are necessary. Significant advances have recently occurred in our understanding of the growth factor and signaling pathways that are active in prostate cancer. In conjunction with this, many new targeted therapies with sound pre-clinical rationale have entered clinical development and are being tested in men with castration-resistant prostate cancer. Some of the most relevant pathways currently being exploited for therapeutic gain are HGF/c-Met signaling, the PI3K/AKT/mTOR pathway, Hedgehog signaling, the endothelin axis, Src kinase signaling, the IGF pathway, and angiogenesis. Here, we summarize the biological basis for the use of selected targeted agents and the results from available clinical trials of these drugs in men with prostate cancer.